Short-term effects of night shift work on breast cancer risk: a cohort study of payroll data - Helene Tilma Vistisen; Anne Helene Garde; Morten Frydenberg; Peer Christiansen; Åse Marie Hansen; Johnni Hansen; Jens Peter Ellekilde Bonde; Henrik A Kolstad (Nordic Association of Occupational Safety and Health (NOROSH), 2017)
OBJECTIVES: The objective was to examine if night shift work is a short-term risk factor for breast cancer, including combined estrogen receptor (ER) and human epidermal growth factor 2 (HER2) breast cancer subtypes. METHODS: The cohort comprised 155 540 public sector female workers in Denmark who were followed from 2007-2012. Day-to-day work-hour information was available from payroll registers and 1245 incident cases of breast cancer were identified in national cancer registries together with receptor subtype information. RESULTS: A rate ratio (RR) of 0.90 [95% confidence interval (95% CI) 0.80-1.01] was observed for workers ever working night shifts during the follow-up period compared with workers only working day shifts after adjustment for age, age at first child, parity, family history of breast or ovarian cancer, sex hormones, medications related to alcoholism, family educational level, mammography screening, and other potential confounders. Comparable results were seen for the inception population of employees with first recorded employment after 2007. Modestly increased RR were suggested for breast cancer subtypes characterized by a positive HER2 status irrespective of ER status. CONCLUSIONS: These findings do not support an overall short-term effect of night shift work on breast cancer risk. Future studies should explore further the impact of HER2 status.